METHODS OF DEVELOPING IDEOLOGICAL-AESTHETIC REFLECTION IN PHILOSOPHICAL EDUCATION (The Conference Hub, 2025)
In this article, the theoretical and methodological foundations as well as practical methods of forming ideological-aesthetic reflection in students’ consciousness within the process of philosophical education are analyzed. The philosophical meaning of the concept of reflection is revealed, and its interrelation with aesthetic perception, spiritual values, and creative thinking is elucidated. In addition, interactive and innovative methods aimed at ensuring the harmony of philosophical thinking and aesthetic emotion in students are proposed.